(untitled) (Interdisciplinary Studies Journal, 2026)
Considering the growing use of smartphones by students in contemporary society and the possibilities of developing digital literacy skills, this paper sought to analyze the students’ perception of the use of smartphones as a pedagogical tool in the final years of elementary school within the context of digital literacy. This is a multi-case study (two cases) in which questionnaires with open and closed questions were administered to 10 students from two public institutions in the city of Parnaíba, Piauí, along with researcher observation. Among the main findings, the primary use of mobile devices during social confinement due to the COVID-19 pandemic stands out, yet there is a gap in the critical and creative use of digital tools in the participating institutions. As a central result, the research was fundamental for broadening knowledge on the subject and allowing recognition of the importance of listening to students and ensuring that the school is attentive to the technological demands that currently contextualize the students’ reality